Communication and Popularization of Science and Technology in China - Ren, Fujun. author. aut Link
XIX, 361 p. 15 illus.
Keywords: This book aims to be a reference for researchers studying the promotion of scientific literacy in China, as well as a guide for those interested in promoting scientific awareness. It covers advances in science and technology, communication and popularization practice, and research (STCP) both in China and abroad. Theoretical issues are discussed, and important problems in promoting scientific and technological awareness are identified (e.g.: basic principles, structures, channels of communication and current needs) This bookprovides a summary of the advances in STCP in China in recent years (especially after the issuing of the “National Scientific Literacy Outline”) including STCP resource and capacity building, science popularization policies, practitioner development, infrastructure construction, and the development of the science popularization industry as a whole. At the same time, this book also reviews thedesign, organization, monitoring and evaluation of science and technology communication and popularization programs. It also highlights current STCP trends and developments in China and calls for a greater emphasis to be placed on research into promoting scientific literacy. It is hoped that this book will be useful to readers both in China and abroad by familiarizing them with the history and theory of STCP as well as its development over time. The 1st chapter briefly reviews the history of STCP. The 2nd through 5th chapters discuss the conceptual framework, basic structure, methods of communication, and current STCP needs. The 6th chapterintroduces the principle content of programs aimed at improving Chinese citizens’ scientific literacy, while the 7th and 8th chapters analyze the resources, capacities and conditions that have been developed for STCP in China. The 9th chapter investigates the organization, monitoring and evaluation of science popularization practices, and the final chapter summarizes important STCP topics and trends in contemporary China.